Pengaruh Pelatihan Dan Kecelakaan Kerja Terhadap Peningkatan Produktivitas Kerja (Kasus PT.Goodyear Indonesia, Tbk Bogor) - Purba, Jan Horas Veryady (Jurnal Ilmiah Ranggagading (JIR), 2002)
The purpose of this research is 1) to delve information regarding how far the influence of training to workers productivity and2) to observed the implementation of K3 obliged by government. Approach conducted to find out the role K3 is from work mishap of workers and how far the influence of work mishap to workers productivity. The essence of this research is in the frame of developing human resources, specifically in an effort to increase human resources productivity in a firm, with PT Goodyear as case study object. Itâs proven from this research that training has significant influence to workers productivity increase. If the firm escalates its training program, workers productivity will be higher. If each of workers get more training program, say an hour, thereby workers productivity will increase 0,0288 tire per workers productivity as well. If work, mishap increase one person, productivity will decrease 0,012 tire per worker per month